Optimizing woodcutting with zirconia-toughened alumina: Processing, performance, and industrial insights - Tamanna Thakur; Stefan Heinen; Bruno Ehrle; Gurdial Blugan (Heliyon)
Since the 1950s, the woodcutting industry has relied heavily on tungsten carbide (WC) cutting tools to overcome the challenges posed by the complex structure of wood, including hard knots and abrasive elements such as sand and tannic acids. These demands require cutting tools with superior thermal conductivity and mechanical properties. However, the rising cost of WC materials has prompted the search for alternative solutions. As a result, zirconia-toughened alumina (ZTA) ceramic materials with varying amounts of in situ formed SrAl12O19 have been introduced as potential substitutes. This study focuses on the processing, microstructural characterization, and mechanical behavior of these ceramic cutting tools with the goal of matching or exceeding the cutting performance and tool life of conventional WC tools. The study demonstrates the effectiveness of the improved ceramic tools through numerical evidence obtained from short-term trials and subsequent extended high-speed tests conducted on industrial cutting machines. In particular, comparable wood surface quality and wear resistance were achieved along with a significant improvement in cutting speed, resulting in a threefold reduction in machining time. These results underscore the potential of ceramic cutting tools as a cost-effective and efficient alternative in the woodcutting industry.